Evaluation of reduced tillage technologies in corn production based on soil and crop analyses - Megyes, Attila; Rátonyi, Tamás; Nagy, János; Kovács, Márta (Acta Agraria Debreceniensis, 2001)
Despite new cultivation methods, the proportion of conventionally cultivated land is still very high in Hungary. Although these technologies demand more time, labour and fuel, they are still attractive to users because they require less professional skill and simple machinery. In Hungary, conventional tillage methods usually lead to soil deterioration, soil compaction and a decrease in organic content. These side effects have caused gradually strengthening economic and environmental problems. The technologies for those plants which are dominant on Hungarian arable lands use (winter wheat, maize, sunflower and barley) need to be improved both in the interest of environmental protection and the reduction of cultivation costs. The Department of Land Use at Debrecen University is cooperating with KITE Sc. to carry out soil tillage experiments at two pilot locations to prove tillage technologies already used in the USA. The aim of our examination is to adapt new technological developments and machinery, and to improve them on Hungarian soil for local environmental conditions. With these improved machines, the field growing of plants could be executed by less manipulation and better suited to economic and environmental needs. The most significant task is to investigate and improve the conventional cultivation replacing, new soil-protecting tillage technologies, and to apply no-till and mulch tillage systems. On the basis of the experiments’ survey data, we established that the looseness and moisture content of the soil using reduced tillage is more favourable than after using conventional technologies. The results of no-till and shallow spring tillage are behind those of winter plough or disk ripper cultivation in corn yield and production elements. To preserve moisture content in the soil, the ground clearing and sowing while simultaneously performing no-till method presents the most favourable results. The surplus moisture gained using no-till technology is equal to 40 mm precipitation. Regarding the yield of winter wheat we established that the tillage methods do not affect plant yield. Both disk ripper and conventional disc cultivation showed nearly the same harvest results (5.55 or 5.5 t/ha), where the difference is statistically hardly verifiable from the no-till method. From the individual production of corn and the number of plants planted in unit area, calculated results prove that no significant difference can be detected between the production of winter plough and disk ripper technology. Although the yield achieved with the no-till method is less than with the previously mentioned technologies, the difference is only 9-10%. We received the lowest production at shallow spring tillage. Evaluations have shown a 1.1 t/ha (13%) difference in the yield of maize, between winter tillage and the disk ripper method, in this case the traditional method resulted in higher yield. In winter tillage, the yield of maize was 1.9-2.1 t/ha (23-25%) higher than in the case of direct sowing and cultivator treatments. No significant difference could be noted between the yields of direct sowing and cultivator treatments. Our research so far has proved the industrial application of reduced tillage methods in crop cultivation technologies.